DAMPAK EKSPLORASI PADA PEMBELAJARAN TARI DI SMP NEGERI 4 KOTA SOLOK - Viska Nanggita; Yuliasma Yuliasma; Susmiarti Susmiarti (SENDRATASIK UNP, 2017)
AbstractThis article aims to reveal and explain the impact of exploration on dance lessons in SMP Negeri 4 Kota Solok. This research will trace the learning process of dance by using exploration. The type of this research is qualitative with descriptive method of analysis, because this research tries to make description, description about a real situation which is in accordance with reality. Data obtained by direct observation and interview, test techniques are not required in this study. The main instrument in this study is the researchers themselves, who became the object of this study is the students of class VIII-B in SMP Negeri 4 Kota Solok. From the result of this research, it is concluded that in the learning of traditional dance in SMP Negeri 4 Kota Solok, the exploration has an impact on supporting the imagination, and the creative power and the ability of students in giving birth to new movements which is the development of motif of traditional dance movement. Another impact is the appearance of self-confidence in students, students have the ability to express simple dance moves performed in groups. Keywords: Exploration, Dance Learning